Integration of Quality Function Deployment and Kano Model in Service Business - Shafira Chaerunnisa Prasetyo, Budi Harsanto (Fakultas Ekonomi dan Bisnis, Universitas Tarumanagara, 2019)
The purpose of this study is to determine the priority of customer requirements and technical responses for restaurants using the Quality Function Deployment (QFD) with the integration of the Kano Model. The data is collected through direct observations, interviews, and surveying of 150 respondents who are customers of restaurant B in Bandung. The data is analyzed by combiningÂ Kano Model with QFD in helping to build the first matrix in the House of Quality, namely the customer input matrix. This matrix together with other matrices forms a complete building of House of Quality. The findings show that there are six service attributes in a 'must-be' category. TheÂ two technical responses that should be prioritized for improvement because their importance level is above average are improvement of the facilities and maintenance of the facilities for the consumers. The two most highlighted facilities include a place of worship that is comfortable and clean, and a larger parking area.